MORPHOMETRIC ANALYSIS OF THE SATY USING THE GIS-TECHNOLOGIES (Journal of Geography and Environmental Management, 2019)
The problem of exodynamic processes occurring in the mountain regions of Kazakhstan is particularly acute. These processes that occurred on the territory of the village of Saty in April 2018 demonstrated that they not only pose a threat to tourist routes laid to mountain lakes but also have serious social, economic and environmental consequences for the lives of people and the security of the economic infrastructure. To determine and predict such processes, it is necessary to know the relief features of the studied area and evaluate both its quantitative and qualitative indicators. To determine the morphometric relief parameters using modern GIS technologies and open access sources, the village of Saty was chosen as an object. In the course of the work, ASTER-GEM images with a resolution of 30 m and ArcGIS software were used. As a result of the study, maps of the slope of the terrain and the exposure of the relief were constructed. It was determined that most of the territory belongs to the area with an average steepness (35%) and steep (30%). The results of the work can be further applied to determine the stability of the slopes to the manifestation of exogenous processes, as well as during landscape zoning and planning in the mountainous regions of the country. Also when assessing environmental risk.
Keywords: morphometric analysis, exodynamic processes, GIS, DEM, Kazakhstan, slope, aspect